"..that warm feeling that [alcohol] gave me was what I interpreted love would feel like.." Lived experience of excessive alcohol use and care proceedings by mothers in the family justice system in the UK. (May 2019) - Boreham, Maggie; Marlow, Sally; Gilchrist, Gail
Abstract: Background: When mothers who have been identified as using alcohol excessively appear in child care proceedings seeking to retain care of, or be reunited with, their children, family courts primarily focus on whether those mothers can make lasting changes to their use of alcohol, very often requiring them to achieve abstinence. The aim of this study was to advance the evidence base around how such mothers make sense of their alcohol use, and their position as mothers, in the systems and processes around care proceedings. Methods: Qualitative, face-to-face interviews were carried out at various children and families' services locations across the UK. These yielded in-depth accounts, to which Interpretative Phenomenological Analysis (IPA) was applied. Results: Six mothers were recruited from collaborations with 31 local authorities. Themes relating to alcohol use included relationships in childhood, repeated traumatic events, and the use of alcohol to self-manage these. In response to extreme fear arising from violence in their relationships with older men, alcohol provided the means to function. Escalation of alcohol use in participants' lives was accompanied by greater isolation, alongside shameful feelings about being a "drunk", which were barriers to help-seeking. Themes relating to motherhood in the context of care proceedings included wanting to change behaviour for themselves and their children, being excluded from their children's lives, and experiencing a continual requirement to prove their parenting and their abstinence from alcohol. Language used by social services, the courts and alcohol treatment services, placed mothers in conflicting positions of being in recovery, but having to present as recovered. Conclusion: Despite excessive alcohol misuse in mothers being closely enmeshed with other issues, awareness and understanding of factors such as complex trauma, and how to support mothers with these factors, is limited, and should be considered in terms of improving research and best practice. Highlights: Mothers appearing in care proceedings characterise their alcohol use as relational. Mothers in care proceedings misusing alcohol describe abusive intimate relationships. Mothers express being taken by surprise at the speed their alcohol misuse escalated. Mothers take action to address their alcohol misuse for themselves and their children. Mothers do not feel they have support from social services addressing alcohol misuse.